Inter IKEA System B.V. / Muhammad Kamal Hafez Haris - Hafez Haris, Muhammad Kamal (2022)
IKEA is one of the world’s largest retailers in the world. They have managed to make their products and services more popular based not only on price but by creating a unique shopping experience for the customers. The IKEA Group belonging to the Foundation Stichting INGKA is the leading supplier and retailer of furniture and home appliances worldwide. IKEA Group was formed by Ingvar Kamprad, Ingvar, seven decades ago in the Swedish southern part of Småland. The purpose of this study is focussing on the home desk that is produced by the IKEA Group that to be investigate, identified, and analysed along with their current problems and come out with solutions. This study will gather general data from the business, including company backgrounds, technologies used, and various types of furnishings produced by the company in the first part of the project study. Through the SWOT review, it will discern the power, vulnerability, opportunities, and risks of the business in the second part of the project study and identify a better approach for technological systems that can be apported in the firm to address the current problems facing the company. In market creation, policy, and preparation for improving the current structure are essential.